2018
DOI: 10.1016/j.jsha.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of memory loss and depression among myocardial infarction patients in Al-Qassim, Saudi Arabia

Abstract: Activity level and poor health were identified as correlates of depression as well as combined memory loss and depression. Future studies should aim to improve screening for depression among post-MI patients and develop appropriate interventions to raise the level of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Thirty-three percent of the participants in our study presented them during their first hospitalization. This is consistent with previous data reporting depression in 20%-40% of MI patients [3]. CI is among the main symptoms of depression, and its presence is a predictor of dementia development [4].…”
Section: Resultssupporting
confidence: 93%
“…Thirty-three percent of the participants in our study presented them during their first hospitalization. This is consistent with previous data reporting depression in 20%-40% of MI patients [3]. CI is among the main symptoms of depression, and its presence is a predictor of dementia development [4].…”
Section: Resultssupporting
confidence: 93%
“…28,29 During this time, it is less likely for patients affected by anxiety and depression to make the necessary changes to their lifestyle, and adhere to their medications. 30 In addition to these potential influences, it is also thought that certain cardiac medications may impact on CI symptoms. Medications such as anticoagulants can improve CI by reducing the risk of cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that women have a notably higher prevalence of depression post-MI compared to men, with 36% in women and 29% in men. However, the all-cause mortality associated with depression is higher in men, and men with depression post-MI have a worse prognosis than women with depression post-MI [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%